Correction to: Nifurtimox versus benznidazole or placebo for asymptomatic Trypanosoma cruzi infection (Equivalence of Usual Interventions for Trypanosomiasis - EQUITY): study protocol for a randomised controlled trial (vol 20, 431, 2019) (2019)
Background: Either benznidazole (BZN) or nifurtimox (NFX) is recommended as equivalent to treat Trypanosoma cruzi infection. Nonetheless, supportive data from randomised trials is limited to individuals treated with BZN in southern cone countries of Latin America. Methods: The goal of this randomised, concealed, blind, parallel-group trial is to inform the trypanocidal efficacy and safety of NFX and its equivalence to BZN among individuals with T. cruzi positive serology (TC+). Eligible individuals are TC+, 20–65 years old, with no apparent symptoms/signs or uncontrolled risk factors for cardiomyopathy and at negligible risk of re-infection. Consenting individuals (adherent to a 10-day placebo run-in phase) receive a 120-day BID blinded treatment with NFX, BZN or matching placebo (2:2:1 ratio). The four active medication arms include (1) a randomly allocated sequence of 60-day, conventional-dose (60CD) regimes (BZN 300 mg/day or NFX 480 mg/day, ratio 1:1), followed or preceded by a 60-day placebo treatment, or (2) 120-day half-dose (120HD) regimes (BZN 150 mg/day or NFX 240 mg/day, ratio 1:1). The primary efficacy outcome is the proportion of participants testing positive at least once for up to three polymerase chain reaction (PCR) assays (1 + PCR) 12–18 months after randomisation. A composite safety outcome includes moderate to severe adverse reactions, consistent blood marker abnormalities or treatment abandons. The trial outside Colombia (expected to recruit at least 60% of participants) is pragmatic; it may be open-label and not include all treatment groups, but it must adhere to the randomisation and data administration system and guarantee a blinded efficacy outcome evaluation. Our main comparisons include NFX groups with placebo (for superiority), NFX versus BZN groups and 60CD versus 120HD groups (for non-inferiority) and testing for the agent-dose and group-region interactions. Assuming a 1 + PCR ? 75% in the placebo group, up to 25% among BZN-treated and an absolute difference of up to ? 25% with NFX to claim its trypanocidal effect, 60–80 participants per group (at least 300 from Colombia) are needed to test our hypotheses (80–90% power; one-sided alpha level 1%).